Review of Clinical Characteristics and Management of Patients with ST Segment Elevation Myocardial Infarction at aTertiary Care Center - Sánchez, Magda; Cox, Rafael A.; Rodríguez, José M.; Pérez, Cynthia M. (Puerto Rico Health Sciences Journal, 2009)
Background: Information from recent multiple trials on the pathophysiology and outcome of ST-segment elevation myocardial infarction (STEMI) has changed its clinical perspective and strategic management, leading to a revision of the 1999 ACC/AHA practice guidelines for that condition. Objective: Analyze the clinical characteristics, management strategies, the timing of therapeutic interventions and outcome of patients with STEMI referred to the Cardiovascular Center of Puerto Rico (CVCPR). Methods: Retrospective review of medical records of all patients admitted to the CVCPR with a diagnosis of STEMI from January 1, 2003 to December 31, 2003. Results: A total of 184 medical records were reviewed. Seventy- six percent of patients were men, mean age was 62.1 ± 11.8 years. A high prevalence of coronary risk factors was present: systemic hypertension (64%), diabetes mellitus (40%), dyslipidemia (35%), smoking (33%) and previous CAD (32%). Less than 1/4 of referral forms contained data indicative of whether patients had received antiplatelet therapy, beta-blockers, ACE inhibitors or statins. Fifty percent of patients arrived to the CVCPR more than 48 hours after diagnosis. Only forty-two patients (23%) arrived within 12 hours. Thrombolytic therapy had been used in 27% of them. 179 (97%) patients underwent coronary angiography, 69.2% of which had multivessel disease. 114 (62%) patients underwent percutaneous coronary interventions (PCI) with stenting. Patients submitted to PCI and stenting of the culprit lesion had a better outcome and survival than the ones not exposed to those procedures (p=0.02). Approximately two-third of patients received secondary prevention medications upon discharge. Conclusions: Relevant findings of this review were that in spite of high prevalence of CAD major risk factors, the use of medications of proven benefit for prevention and treatment of CAD at referral centers was less than that recommended by current guidelines, a significant delay in the transfer of patients to the tertiary care facility (in most cases that period exceeded more than 48 hours after diagnosis) and a reduced utilization of thrombolytic therapy. Intensification of the education of physicians throughout the island regarding these matters is to be encouraged. Additional measures should include, development of written protocols at referral centers to assure a more expedite clinical assessment of patients, an enhancement of their capability for utilizing fibrinolytic agents in suitable candidates and the timely transfer to PCI-capable facilities of patients that may still benefit from catheter reperfusion.